PLP1 Gene Variation Modulates Leftward and Rightward Functional Hemispheric Asymmetries - Ocklenburg, Sebastian; Gerding, Wanda M; Raane, Maximilian; Arning, Larissa; Genç, Erhan; Epplen, Jörg T; Güntürkün, Onur; Beste, Christian (Molecular neurobiology, 2018)
Molecular neurobiological factors determining corpus callosum physiology and anatomy have been suggested to be one of the major factors determining functional hemispheric asymmetries. Recently, it was shown that allelic variations in two myelin-related genes, the proteolipid protein 1 gene PLP1 and the contactin 1 gene CNTN1, are associated with differences in interhemispheric integration. Here, we investigated whether three single nucleotide polymorphisms that were associated with interhemispheric integration via the corpus callosum in a previous study also are relevant for functional hemispheric asymmetries. To this end, we tested more than 900 healthy adults with the forced attention dichotic listening task, a paradigm to assess language lateralization and its modulation by cognitive control processes. Moreover, we used the line bisection task, a paradigm to assess functional hemispheric asymmetries in spatial attention. We found that a polymorphism in PLP1, but not CNTN1, was associated with performance differences in both tasks. Both functional hemispheric asymmetries and their modulation by cognitive control processes were affected. These findings suggest that both left and right hemisphere dominant cognitive functions can be modulated by allelic variation in genes affecting corpus callosum structure. Moreover, higher order cognitive processes may be relevant parameters when investigating the molecular basis of hemispheric asymmetries.
Keywords: akustická stimulace; dospělí; funkční lateralita; dichotické testy; Female; Genotype; pozornost; Acoustic Stimulation; Adult; Functional Laterality; mladý dospělý; ženské pohlaví; jednonukleotidový polymorfismus; Adolescent; Attention; myelinový proteolipidový protein; lidé; Polymorphism, Single Nucleotide; genotyp; Dichotic Listening Tests; Myelin Proteolipid Protein; Male; Aged; Young Adult; velký mozek; lidé středního věku; senioři; mužské pohlaví; Cerebrum; Middle Aged; mladiství; Humans